Electrovocal Music: eroticism, electromagnetisms, and vocalities (Palíndromo, 2025)
The concept of "electrovocal" (Bossi, 2005; Bosma, 2013; Mendes, 2018; Holmes, 2022) can serve as a trigger to address aspects of agency in enunciation and eroticism in the use of the voice in electronic and electroacoustic music, especially vocalized and composed by women. Eroticism here is an ethical term to designate a sense for affective, incorporeal components present in relational exchanges, but also in materials of meaning, in the heterogeneous components between sound, voice, instruments, and technological devices. It is present in the resonant breath of vocality that incorporates the logos (Cavarero, 2014) and in the poetic word, according to Octavio Paz (1994). Desire and eroticism are potent as agency and the agency of the voice and electronics. Agency as the minimal real unit that produces enunciations, always collective, that puts into play, in and outside of us, populations, multiplicities, territories, becomings, affects, events (Deleuze; Guattari, 1995).
Keywords: Eletrovocal; eroticism; eletroacoustic music; assemblage; vocalities